Transition from nonsequential to sequential double ionization in many-electron systems - Pullen, Michael G.; Wolter, Benjamin; Wang, Xu; Tong, Xiao-Min; Sclafani, Michele; Baudisch, Matthias; Pires, Hugo; Schröter, Claus Dieter; Ullrich, Joachim; Pfeifer, Thomas; Moshammer, Robert; Eberly, J. H.; et al. (My University, 2017)
Understanding strong-field double ionization of many-electron systems is an important fundamental problem with potential implications for molecular imaging within this regime. Using mid-IR radiation, we unambiguously identify the transition from nonsequential (e, 2e) to sequential double ionization in Xe at an intensity below 1014W/cm2. Ionization from excited orbitals is found to be decisive at low intensities, but we demonstrate that such mechanisms are unimportant in the sequential regime. We utilize these facts to successfully image a molecular dication using laser-induced electron diffraction. This methodology can be used to study molecular dynamics on unprecedented few-femtosecond time scales.
Keywords: Electron & positron scattering; Electron correlation calculations for atoms & ions; Multiphoton or tunneling ionization & excitation; Ultrafast phenomena